(untitled) (Indonesian Journal Of Social Issues and Multidisiplinary Studies, 2026)
The rapid development of information technology has increased reliance on digital data in various individual and organizational activities. This condition was accompanied by a growing number of cybersecurity threats, particularly malware attacks targeting local storage systems. Although cloud-based services have continued to expand, local storage was still widely used due to the full control it provided over data. However, such systems showed a high level of vulnerability when they were not supported by adequate security mechanisms. This study aimed to examine data security in local storage systems against malware threats through a literature-based analysis. The research method used was descriptive qualitative with a literature review approach, drawing data from scientific journals, reference books, and cybersecurity reports. The results indicate that malware such as viruses, trojans, spyware, and ransomware poses significant threats to the principles of Confidentiality, Integrity, and Availability (CIA) in local storage systems. Therefore, the implementation of layered data security, through the use of antivirus software, data encryption, access control, regular data backups, and increased user awareness, plays an essential role in minimizing malware risks and maintaining the security of local storage systems.